PERFORMA SAPI POTONG SEBAGAI RESPON DARI SUPLEMENTASI PROBIOTIK PADAT DAN CAIR - Dian Purwanti; Suryahadi Suryahadi; Dwierra Evvyernie Amirroenas (Buletin Ilmu Makanan Ternak, 2014)
(PERFORMANCE OF BEEF CATTLE IN RESPONSE TO SOLID AND LIQUID PROBIOTIC SUPPLEMENTATION)Probiotics are live microbial feed supplements form, providing beneficial effects for the host animal by improving the balance of microorganisms in the digestive tract. This study aims to examine the benefits of probiotic supplementation in the form of liquid and solid on performance of beef cattle. The treatment used is as follows: P1: Ration Control (forage + concentrate + rice bran), P2: Ration Control + 0.25% solids probiotic in the concentrate, P3: Ration Control + 1% liquid probiotic through drinking water. Experimental design used was Randomized Block Design with 18 cows that are divided into six groups based on body weight and 3 treatment ration. Parameters measured were consumption of nutrients, body weight gain, efficiency of feed utilization, and Income Over Feed Costs (IOFC). The collected data were analyzed by analysis of variance. The test results statistically showed that the treatment was not significant (P> 0.05) effect on the consumption of nutrients, body weight gain and efficiency of feed utilization. Keywords: beef cattle, liquid probiotics, performance, solid probiotics